Impact of Wheat-Derived Rhizobacteria on the Maize Development from District Bajaur, Khyber Pakhtunkhwa, Pakistan - Asia Bibi; Saima Ashraf; Nosheen Azhar; Sidra Qayyum; Masab Saeed; Rida Zameer; Hifsa Arif; Syed Azhar Shah Kazmi; Asim Shahzad (Al-Qanṭara, 2025)
This study investigates the potential of rhizospheric bacteria isolated from wheat plants in Bajaur, Khyber Pakhtunkhwa, Pakistan, for promoting maize growth. A total of 12 bacterial strains, including Pseudomonas canadensis (RW-2), Enterobacter ludwigii (RW-5), and Bacillus aerius (RW-12), were isolated from the rhizosphere, rhizoplane, and endophytic regions of wheat plants. These strains were characterized based on their morphological and biochemical properties, including phosphate and potassium solubilization, catalase activity, nitrogen fixation, and indole acetic acid production. The bacterial strains were further tested for their compatibility in a consortium and their effect on maize growth in a greenhouse experiment. The results showed that Pseudomonas canadensis and Bacillus aerius exhibited significant phosphate and potassium solubilization activity, while Enterobacter ludwigii was effective in producing IAA. The greenhouse experiment revealed that the application of bacterial consortia combined with 90% potassium increased maize plant height by 25%, root length by 42%, and leaf area by up to 48% compared to control treatments. The results suggest that the isolated rhizospheric bacteria significantly enhanced maize growth, offering a sustainable alternative to chemical fertilizers.